2023
DOI: 10.3389/fcvm.2023.1117419
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-related differences in the inflammatory properties of cardiac fibroblasts: impact on the cardiosplenic axis and cardiac fibrosis

Kathleen Pappritz,
Sarah-Lena Puhl,
Isabel Matz
et al.

Abstract: BackgroundAge and sex are prominent risk factors for heart failure and determinants of structural and functional changes of the heart. Cardiac fibroblasts (cFB) are beyond their task as extracellular matrix-producing cells further recognized as inflammation-supporting cells. The present study aimed to evaluate the impact of sex and age on the inflammatory potential of cFB and its impact on the cardiosplenic axis and cardiac fibrosis.MaterialsLeft ventricles (LV) of 3- and 12-months old male and female C57BL/6J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…They showed that while reactive fibrosis in the myocardium and epicardium is seen in the aged hearts of female mice, perivascular and replacement fibrosis are observed in male hearts. Pappritz et al [132] report that the collagen content of female cardiac fibroblasts is higher in 12-month-old animals. These observations point to the need for gender-dependent anti-fibrotic management in the elderly population.…”
Section: Dysregulated Collagen Turnover Promotes Excessive Collagen D...mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that while reactive fibrosis in the myocardium and epicardium is seen in the aged hearts of female mice, perivascular and replacement fibrosis are observed in male hearts. Pappritz et al [132] report that the collagen content of female cardiac fibroblasts is higher in 12-month-old animals. These observations point to the need for gender-dependent anti-fibrotic management in the elderly population.…”
Section: Dysregulated Collagen Turnover Promotes Excessive Collagen D...mentioning
confidence: 99%
“…The study showed that immune cells, mostly macrophages, accumulate in the old ventricle and show morphological and behavioural changes, impacting response to injury. It has recently been shown that age-and sex-dependent variations in inflammatory properties in cardiac fibroblasts lead to age-and sex-dependent differences in cardiac fibrosis and inflammation [132].…”
Section: Myocardial Aging and Impaired Immune Response To Injurymentioning
confidence: 99%